Increasing Coverage of Hepatitis B Vaccination in China: A Systematic Review of Interventions and Implementation Experiences. Issue 19 (May 2016) - Wang, Shengnan; Smith, Helen; Peng, Zhuoxin; Xu, Biao; Wang, Weibing
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: This study used a system evaluation method to summarize China's experience on improving the coverage of hepatitis B vaccine, especially the strategies employed to improve the uptake of timely birth dosage. Identifying successful methods and strategies will provide strong evidence for policy makers and health workers in other countries with high hepatitis B prevalence. We conducted a literature review included English or Chinese literature carried out in mainland China, using PubMed, the Cochrane databases, Web of Knowledge, China National Knowledge Infrastructure, Wanfang data, and other relevant databases. Nineteen articles about the effectiveness and impact of interventions on improving the coverage of hepatitis B vaccine were included. Strong or moderate evidence showed that reinforcing health education, training and supervision, providing subsidies for facility birth, strengthening the coordination among health care providers, and using out-of-cold-chain storage for vaccines were all important to improving vaccination coverage. We found evidence that community education was the most commonly used intervention, and out-reach programs such as out-of-cold chain strategy were more effective in increasing the coverage of vaccination in remote areas where the facility birth rate was respectively low. The essential impact factors were found to be strong government commitment and the cooperation of the different government departments. Public interventions relying on basic health care systems combined with outreach care services were critical elements in improving the hepatitis B vaccination rate in China. This success could not have occurred without exceptional national commitment.